Bibliometric Analysis of Halal Industry Research in the Global Market - Judijanto, Loso; Solihin, Dadin; Nurnaningsih, Rita; Yusniar, Yusniar; Gastriani, Ovi Prina (Westscience Press, 2025)
The halal industry has become a vital component of the global market, driving significant interest among researchers and practitioners. This study conducts a bibliometric analysis of halal industry research using data from the Scopus database and VOSviewer software. Key findings reveal the centrality of themes such as halal certification, logistics, and supply chain management, highlighting their importance in operational and consumer trust frameworks. The analysis identifies Malaysia and Indonesia as leading contributors to halal research, with strong international collaborations. Emerging trends, including blockchain, sustainability, and halal tourism, signify the evolving focus of the halal industry toward technological integration and ethical practices. The study also highlights knowledge gaps, such as the underrepresentation of non-food sectors and limited exploration of regional dynamics outside Southeast Asia. By addressing these gaps, this study provides a foundation for advancing halal industry research and fostering global collaboration.